Evaluation of Multi-Cloud Strategies and Challenges in Small-Scale Organizations - Ganesan, Arun Prakash (Digital Repository of Theses, 2024)
Multi-cloud computing is emerging as a promising paradigm for providing abundant computation resources for medium and large-scale organization. While most cloud providers provide similar functionality, performance and/or cost may vary significantly. A customer who wants to take advantage of such differences will naturally want to solve the multi-cloud configuration problem given a workload, which cloud provider should be chosen, and how should its nodes be configured to minimize runtime or cost. This research is being conducted to explore and understand how certain large and medium scale organization achieved success through multi-cloud business strategies. The goal is to analyses data from interviews conducted with senior leaders in the IT industry and business leaders. The Leaders have influence over storage, cloud, and/or data management technology decisions in their organization. obtaining details about how they are utilizing cloud infrastructure to promote innovation while also limiting cloud costs and evaluating the resulting business advantages for future start-ups. In the same space to increase their chances of leveraging multi-cloud computing and getting the most out of each cloud service in order to increase productivity, provide exceptional customer service, and scale their business to the next level. In general, the multi-cloud strategy for small business success.